Dry Eye Cross-Sectional Study – Philippines: Comparison with the Asia Dry Eye Society Criteria and OCULUS Keratograph 5M Findings - Ruben Lim Bon Siong, MD; Bobbie Marie Santos, MD; Keshia Duyongco-Lenon, MD; Jessica Marie Abaño, MD; Reynaldo Santos, MD; Ivo John Dualan, MD (Philippine Journal of Ophthalmology, 2025)
Objective: This study compared the proportion of dry eye disease (DED) diagnosed using the Philippine criteria with that diagnosed using the Asia Dry Eye Society (ADES) criteria among participants, and characterized DED features using clinical tests and the OCULUS Keratograph® 5M (K5M; OCULUS Optikgeräte GmbH, Wetzlar, Germany).